Pengaruh Kualitas Produk dan Harga pada Keputusan Pembelian dengan Kepercayaan Konsumen sebagai Variabel Mediasi: Studi pada Konsumen Rocket Chicken di Kota Yogyakarta - Vincka Ambarwati; Muhammad Mathori (Universitas Nusantara PGRI Kediri, 2024)
For Indonesians, fried chicken is a popular food that has been served in several foreign fast food restaurants that are now popular in Indonesia. Many entrepreneurs have partnered with Rocket Chicken including in the city of Yogyakarta and have opened several outlets to meet customer needs. This study intends to determine how product quality and price affect purchasing decisions, using customer trust as a mediating factor. By utilizing a quantitative approach, Rocket Chicken customers in Yogyakarta became the following study population, related to the number of samples totaling 119. Tested using Smart PLS. The study results prove: 1) a score statistic of 1.965 indicates that purchasing decisions have a positive effect on product quality. 2) a t-statistic value of 3.742 indicates that price is positively influenced by consumer purchasing decisions. 3) a t-statistic value of 5.54 proves that product quality is positively influenced by consumer trust. 4) a t-statistic value of 4.477 proves that price is positively influenced by consumer trust. 5) t-statistic score of 2.982 proves that consumer trust has a positive influence on purchasing decisions. 6) VAF score of 0.439 shows that consumer trust is not the only mediating variable that influences the relationship between product quality and purchasing decisions. 7) VAF value of 0.303 proves that consumer trust is not the only mediating variable that influences the relationship between price and purchasing decisions. Both variables are included in the partial category.